2020
DOI: 10.1101/2020.07.04.184861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NCBP3 is a productive mRNP component

Abstract: AbstractThe nuclear Cap Binding Complex (CBC), consisting of Nuclear Cap Binding Protein 1 (NCBP1) and 2 (NCBP2), associates with the nascent 5’cap of RNA polymerase II transcripts and impacts RNA fate decisions. Recently, the C17orf85 protein, also called NCBP3, was suggested to form an alternative CBC by replacing NCBP2. However, applying protein-protein interaction screening of NCBP1, 2 and 3, we find that the interaction profile of NCBP3 is distinct. Whereas NCBP1 and 2 ide… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…This data demonstrates that NCPB3 differs from NCBP1 and NCBP2 in selectivity, coprecipitating with members of the THO/TREX complexes. These interactions were later confirmed as supporting a biological role for NCBP3 in mRNA expression that differs from NCBP1 and NCBP2 351. (A) Figure reproduced and adapted with permission from ref 352.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This data demonstrates that NCPB3 differs from NCBP1 and NCBP2 in selectivity, coprecipitating with members of the THO/TREX complexes. These interactions were later confirmed as supporting a biological role for NCBP3 in mRNA expression that differs from NCBP1 and NCBP2 351. (A) Figure reproduced and adapted with permission from ref 352.…”
mentioning
confidence: 88%
“…These interactions were later confirmed as supporting a biological role for NCBP3 in mRNA expression that differs from NCBP1 and NCBP2. 351 isotope labeling methods. These methods rely on the fact that peptides with the same sequence but different isotope enrichment will coelute but be separated in a single spectrum for quantification.…”
Section: Sample Separation and Fractionationmentioning
confidence: 99%
“…ZC3H11A is an RNA-binding protein with three uncharacterized CCCH-type zinc finger motifs (ZFM) motifs present at the N-terminus of the protein (3). Several studies have shown that ZC3H11A is a subunit of the Transcription-Export (TREX) complex, which is responsible for the nuclear mRNA export (4)(5)(6)(7)(8)(9). TREX is a multiprotein complex containing the hexameric core THO complex (THOC1, THOC2, THOC3, THOC5, THOC6, THOC7), which in turn associates with several subunits including ZC3H11A (8).…”
Section: Introductionmentioning
confidence: 99%